A NEW METRIC FOR ASSESSING THE “S” DIMENSION IN ENVIRONMENT, SOCIAL, GOVERNANCE (ESG) FOR REAL ESTATE - Ni Putu Jessica Anggi Wijaya Putri; Ni Kadek Sinarwati; Made Aristia Prayudi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The Environmental, Social, and Governance (ESG) framework has become a central benchmark for assessing corporate sustainability, particularly in the real estate sector. However, the Environmental (E) dimension continues to dominate both measurement and reporting practices, while the Social (S) dimension remains underdeveloped due to the lack of standardized and impact-oriented metrics. This study aims to examine the role of the social dimension in ESG and its implications for sustainability accounting practices in the Indonesian real estate finance sector. Using a quantitative descriptive-explanatory approach, the study analyzes corporate sustainability reports and applies content analysis to evaluate the extent to which social aspects are disclosed and measured. The findings reveal that although companies have increasingly adopted social initiatives such as diversity, employee well-being, and community engagement these efforts are largely activity-based and disclosure-oriented, rather than focused on measurable social impact. Furthermore, ESG assessments are still predominantly based on aggregate scores, which obscure the specific contribution of the social dimension. This study identifies a critical gap in existing ESG measurement frameworks and proposes the need for developing new, impact-based, and context-specific social metrics. Such metrics are essential to enhance the accuracy, transparency, and practical relevance of ESG evaluations, particularly in the real estate sector where social interactions and community impacts are highly significant.